EFFECT OF DENTURE CLEANSERS ON THE COLOR STABILITY OF DIFFERENT DENTURE TEETH MATERIALS - Bora Bağış; Elif Aydoğan Ayaz; Evşen Tamam; Fatih Korkmaz; Sedanur Turgut (Cumhuriyet University, 2014)
Purpose: Denture cleansers are commonly used for cleaning partial and complete dentures. The purpose of this in vitro study was to evaluate the effect of denture cleansers on color stability of conventional acrylic, reinforced acrylic and porcelain denture teeth materials. Material and methods: Maxillary central incisors in A2 color were used from three types of denture teeth (n=10). Denture teeth kept in distilled water were considered as control group. Test specimens were immersed in denture cleansers, which prepared according to the manufacturers instructions. Color measurements were performed before immersion of cleansers, after 1 week and after 3 weeks with a colorimeter. Color changes (ΔE) of the specimens were calculated and the results were compared statistically with three way ANOVA. Results: Significant differences were found on the color changes of denture teeth after 1 week and 3 weeks of the immersion of denture cleansers (p<0,05). Also ΔE values were increased significantly with time (p<0,05). The lowest ΔE values were observed in distilled water. The lowest ΔE values were observed in porcelain teeth in all denture cleansers (p<0,05). Color changes of conventional acrylic and reinforced acrylic teeth in all denture cleansers after 3 weeks were acceptable. Conclusion: The greatest color change was observed in conventional acrylic resin teeth, reinforced acrylic and porcelain teeth, respectively, after immersion of denture cleansers.